2012
DOI: 10.1021/pr201169q
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Extraction Methods for the Comprehensive Analysis of Mouse Brain Proteome using Shotgun-based Mass Spectrometry

Abstract: This study compares 16 different extraction methods for the comprehensive extraction of mouse brain proteome in combination with "shotgun"-based mass spectrometry (MS). Membrane proteins (MPs) are responsible for a large part of the regulatory functions of the cell and are therefore of great interest to extract and analyze. Sixteen protein extraction protocols were evaluated in regards to protein yield and number of identified proteins with emphasis on MPs. The extracted proteins were delipidated, on-filter di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 47 publications
(106 reference statements)
3
47
0
2
Order By: Relevance
“…Taking into account the reported distinct subcellular localizations of C9ORF72 isoforms with localization of C9-S to the nuclear membrane and C9-L in the cytoplasm (Xiao et al, 2015), lysis protocols were investigated. We found that Triton X-100 facilitated the extraction of the C9ORF72 proteins, in agreement with higher extraction yield reported with detergent based protocols in comparison to organic solvents or chaotropic reagents such as urea, in fatty tissue such as the brain (Shevchenko et al, 2012). In addition, the Triton X-100 protein extraction protocol probably enhanced the subsequent trypsin digestion as previously reported (An et al, 2015).…”
Section: Discussionsupporting
confidence: 87%
“…Taking into account the reported distinct subcellular localizations of C9ORF72 isoforms with localization of C9-S to the nuclear membrane and C9-L in the cytoplasm (Xiao et al, 2015), lysis protocols were investigated. We found that Triton X-100 facilitated the extraction of the C9ORF72 proteins, in agreement with higher extraction yield reported with detergent based protocols in comparison to organic solvents or chaotropic reagents such as urea, in fatty tissue such as the brain (Shevchenko et al, 2012). In addition, the Triton X-100 protein extraction protocol probably enhanced the subsequent trypsin digestion as previously reported (An et al, 2015).…”
Section: Discussionsupporting
confidence: 87%
“…For this comparative study we selected an in gel digest method adapted from 19 , conducted in combination with an SDS-based and native protein extraction, two filter-aided ( FASP (Filter Aided Sample Preparation) adapted from 32 and a recent enhancement termed eFASP adapted from 33 , and two in solution procedures (RapiGest, adapted from 22 , and RapidACN adapted from 16 ). Their characteristics are summarized in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…For both protocols the digestion was performed directly on filters (Amicon Ultra-0.5 Centrifugal Filter Unit with Ultracel-3 membrane, Millipore). The FASP procedure ( Supplementary protocol 3) involved a treatment with endoproteinase Lys-C (Promega) prior to digestion with trypsin 20 , while the eFASP protocol ( Supplementary protocol 4) required protein precipitation using tri-n-butylphosphate/acetone/methanol mix (1:12:1) for lipid removal before digestion 21 . For in solution digest protocols ( Supplementary protocol 5 and Supplementary protocol 6) protein extraction was performed either in 200 µl lysis buffer (0.1 M NaOH, 0.05 M EDTA, 2% SDS, 2% β-mercaptoethanol) (RapiGest) or 0.05 M ammonium bicarbonate (RapidACN) 20 and using heat or glass-bead lyses on a Fast-Prep 24 instrument (MP Biomedicals), respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The average of median peak widths from two technical replicates was approximately 38 s with 75% identified peptides eluted within 50 s. Based on this data, we tested the effect of 4 different DE duration settings: 15 s, 30 s, 50 s, and 90 s, on the number of identified peptides ( Table 2). The number of peptide identifications rose by nearly 18% when the DE duration increased from 15 s to 50 s, but There are other parameters in our protocol that were not necessarily fully optimized including the selection of protein exaction lysis buffers [21,24], enzymes and protocols for protein digestion [25][26][27], and peptide fractionation methods [28][29][30].…”
Section: Optimization Of Lc-ms/ms Parametersmentioning
confidence: 99%